(untitled) (KONFERENSIYA, 2025)
This study offers a comparative linguocultural analysis of vulgar and taboo expressions in English and Uzbek, examining how semantic fields of profanity reflect underlying cultural values, social norms, and communicative practices. Using corpora compiled from films, television subtitles, social media discourse, and colloquial programming, vulgar expressions were categorized into seven semantic domains and analyzed for frequency and usage patterns. Findings show that English profanity is dominated by sexual and excretory vocabulary, reflecting secular, individualistic cultural orientations and the historical erosion of religious taboos. In contrast, Uzbek vulgarity centers on personal and kinship-based insults, highlighting the importance of familial honor and collectivist social structures; sexual profanity commonly appears in mother-insult constructions, and religious profanity is largely avoided. Nonverbal insults likewise exhibit culturally specific patterns, with gestures differing in meaning and offensive intensity across the two cultures. Gendered patterns also emerge: Uzbek men employ harsher, dominance-oriented curses, while women tend to use softer or positive “blessing-type” expressions. Overall, the study demonstrates that profanity functions not merely as linguistic aggression but as a culturally meaningful system of emotional expression, social regulation, and identity construction